2021
DOI: 10.2478/afepuc-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory Learning Research: Problem-Based Learning or Project-Based Learning?

Abstract: Summary Problems in learning are one of the obstacles to student’s success in understanding and achieving success. Learning problems also occur in physical education learning, the problems that have occurred in the last decade are caused by the individual students. To minimize and even overcome these learning problems an appropriate learning approach model is needed. In the last 5-10 years, the learning approach models that are often used are problem-based learning and project-based learning. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Rillero and Chen stated that PBL is a learning model that can integrate various subjects with meaningful experiences (Sekarwangi et al, 2021). The PBL learning model can arouse the spirit of critical thinking in students to find solutions to their problems (Naviri et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Rillero and Chen stated that PBL is a learning model that can integrate various subjects with meaningful experiences (Sekarwangi et al, 2021). The PBL learning model can arouse the spirit of critical thinking in students to find solutions to their problems (Naviri et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This issue has become one of the teachers' difficulties in implementing PBL. It's because studies by Naviri et al (2021) indicated that teachers had trouble motivating students who had previously attended a big PBL classroom. Overall, students think that implementing PBL in their academic writing courses should be more appealing to students' interests.…”
Section: Students' Teamworkmentioning
confidence: 99%
“…Pendidikan merupakan hak setiap warga negara, oleh karena itu pendidikan harus diperoleh setiap warga negara tanpa terkecuali. Pemerintah menyadari bahwa penyelenggaraan pendidikan yang bermutu dan universal merupakan sebuah tantangan (Navitri, Sumaryanti & Paryadi, 2022). Pada dasarnya setiap anak berpotensi mengalami permasalahan dalam belajar, hanya saja permasalahan tersebut ada yang ringan atau tidak memerlukan perhatian khusus dari orang lain karena dapat diatasi sendiri oleh siswa dan ada juga yang permasalahan belajarnya cukup berat sehingga perlu mendapatkan perhatian dan bantuan dari orang lain (Buhari, Paryadi & Cahyono, 2021).…”
Section: Pendahuluanunclassified